Evaluating the dependency of neutron spectra and absorbed dose rates on the collimation field size in fast neutron therapy - A.M. Shehada (Elsevier, 2021)
The aim of this research was to investigate the relationship between the collimator aperture and fast-neutron flux, neutron-energy spectrum and absorbed dose rate. For remote therapy, rather large fluxes of fast neutrons are needed which can create dose levels in the tissues of at least 0.1 Gy/min with a source-patient distance of 1 m. Advantageously for these purposes, the 9Be(d, n) reaction was investigated with deuteron energy of 13.6 MeV. The mean energy of the outgoing neutrons was obtained using the code PACE 4 (LISE++) which gave the value of about 5.2 MeV. The maximum neutron flux was at an energy of about 2.5 MeV. Samples activation analysis was deployed to measure the neutron flux in the energy-region [0–14 MeV]. The experimental works were carried out using Al, Fe, Cu and Cd foils which installed on the collimator apertures. To investigate the neutron spectrum, fluxes, and dose rates absorbed at the position of patients, experiments were conducted for four different neutron irradiation-field sizes, which can be modified by the removable-polyethylene parts. Simulation results obtained by the code MCNP-4C and PACE4 (LISE++) were comparable with the experimental data to some extent with consideration of some uncertainties of PACE4 results. It can be concluded that the neutron flux is depended on the irradiation-field size where the neutron flux output for bigger aperture size was about +25% comparing with the smaller ones. These results could play a significant role in improving the neutron flux and optimizing the collimation system utilized in fast neutron therapy. In addition, this can lead to optimization of irradiation canals installed in the nuclear reactors which employed for production of medical isotopes, material testing and many other applications.